Submerge impingement cooling for the high thermal flux electric board - Wong, Yong Jian (Nanyang Technological University, 2021)
For internal cooling to take place, jet impingement cooling technique was first introduced in the early 1960s. although it is a complicated technique, it is also the most efficient method when a high heat transfer rate is needed. Therefore, jet impingement cooling is used widely in the industries. Technologies advances rapidly together with the need of mankind. The size of the electronic chips is getting smaller and smaller as technologies advances and large amount of heat fluxes are being dissipated. Researchers wants to perform submerged jet impingement cooling technique on electronic chips and at the same time determine the effectiveness of such cooling method on it. The obtained heat transfer coefficient and the change in temperature are the main parameter that will be used to analyse the capability of heat transfer in submerged jet impingement cooling technique. The different sizes of the nozzle diameter were found to cause impact to the performance of submerged jet impingement cooling. Thus, it is a critical factor that must be explored in the report. This report consists of both experimental analysis and computation fluid dynamics analysis which will simulate the actions of thermo-fluids in a system. To verify the effectiveness of the jet, this study compares the data collected from the physically conducted experiment and the simulation done with computational fluid dynamics. The experiment and simulation are design such that submerged jet impingement cooling will be performed on a 20mm-by-20mm plain copper block which will be heated by a power source. Further studies can be conducted with different boundary conditions such as different surface finish of the copper block, different nozzle-to-copper surface height, different Reynolds numbers or different subcooling fluid. This will determine which boundary condition is able to give rise to the best heat transfer performance.